2004
DOI: 10.1071/ea02217
|View full text |Cite
|
Sign up to set email alerts
|

The potential for extended lactations in Victorian dairying: a review

Abstract: This review examines the potential for extended lactations on Victorian dairy farms in the context of (i)�the advantages and disadvantages of existing seasonal milk production systems; (ii) projected future changes to Victorian dairy farming; (iii) the mechanics of extended lactations; (iv) the change in costs associated with extended lactations; and (v) how extended lactations might be successfully implemented. Traditionally, Victorian dairying has been characterised by seasonal, low input, pasture-based milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…They found no significant decrease in daily milk yield but, importantly, they observed economic advantages in cows with extended lactations. Other reports from Sweden [29] and Australia [30] also concluded that extended lactations are a suitable option for some enterprises, and that suitability will depend on various factors, particularly cow milk production and especially persistency (the rate of decline in milk yield from peak), as well as management.…”
Section: Extended Lactation: Fine Tuning the Calving Interval-a Possimentioning
confidence: 99%
“…They found no significant decrease in daily milk yield but, importantly, they observed economic advantages in cows with extended lactations. Other reports from Sweden [29] and Australia [30] also concluded that extended lactations are a suitable option for some enterprises, and that suitability will depend on various factors, particularly cow milk production and especially persistency (the rate of decline in milk yield from peak), as well as management.…”
Section: Extended Lactation: Fine Tuning the Calving Interval-a Possimentioning
confidence: 99%
“…Furthermore, almost all cows are milked for about 300 days and are dried off at a pre-determined date. Recently, the seasonal calving system is being challenged due to increased herd size, increased use of bought-in feed, premium paid for off-season milk, increased milk production potential, reduced reproductive performance and pressure from animal welfare groups to minimise induced calving (Borman et al, 2004). As a result of these factors, interest in milking cows beyond the standard 305 days (over an extended lactation period) has increased and the proportion of herds that practice seasonal calving in Victoria, Australia, has decreased from 63% to 41% (Auldist et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2 Estrus_AI: number of insemination at estrus, not counting the double AI at estrus. 3 Total AI: total number of AI per pregnancy, counting the double AI at estrus. 4 Estrus_PR 1 or PR 2 : pregnancy rates at first and second AI (with the first AI defined as estrus_AI).…”
Section: Double Insemination Techniquementioning
confidence: 99%
“…More artificial inseminations (AI) in successive estruses are now needed to obtain pregnancy which is then involuntarily delayed [3]. This increase of reproductive failure and number of AI needed per pregnancy might be partly due to a decrease of estrus behavior, which makes it difficult to detect estrus and to inseminate the cow at the right stage [4].…”
mentioning
confidence: 99%